Status of Dietary Electrolyte Balance in Commercial Poultry Diets in Pakistan - Ahmed, Naveed; Khan, Sohail Hassan; Anjum, Muhammad Ashraf; Sardar, Rozina; Amer, Mohammad Yasin; Amin, Muhammad; Chauhan, Zafar Iqbal; Anjum, Muhammad Yaqoob (Pakistan Journal of Nutrition, 2013)
Dietary Electrolyte Balance (DEB) plays a vital role in body’s homeostasis and optimum provision of DEB which is critical for maximum efficiency and stress coping in birds. A total of 68 poultry feed samples were collected from Multan, Rawalpindi and Sargodha districts of Punjab province of Pakistan. The study included 16 broiler, 16 breeder and 36 layer diets. Water samples (n = 51) alongwith feed samples were also collected wherever possible. These samples were examined for sodium (Na+), potassium (K+) and chloride (Cl-) ions contents and DEB was calculated by subtracting anions from cations. The results showed variations and discrepancies in provision of individual ions as well as overall DEB. These results were compared with National Research Council (1994) recommendations for ionic contents and DEB level was compared by findings of other research studies. The mean of Na+ contents were well within recommended range; Cl- contents were slightly high while K+ contents were 2 to 4 times higher than NRC (1994) recommendations. However the resulting DEB for broiler, breeder and layer flocks was 192.7, 168.1 and 198.2 mEq/kg, respectively. The water can play important role in supplementation of anions and cations thus effecting overall DEB. The 13, 23 and 15 water samples (total = 51) collected from Multan, Rawalpindi and Sargodha districts, respectively showed an area wise distribution pattern of these ions. The mean of Na+ contents of water samples collected from Multan district was 229 ppm as compared to recommended level of 50 ppm for poultry consumption. Whereas analysis of water samples collected from Rawalpindi and Sargodha district showed much better ionic composition for poultry usage.